The response of a flat plate boundary layer to an orthogonally arranged dielectric barrier discharge actuator - Gibson, Brad; Arjomandi, M.; Kelso, R. (IOP Publishing Ltd, 2012)
The jetting characteristics of dielectric barrier discharge (DBD) actuators make these devices suitable for augmenting boundary layer flows. The associated change to the hydrodynamic stability of the fluid arising from the actuator provides a mechanism through which a DBD-based laminar flow control (LFC) system can be developed. Historically, DBD actuators with electrodes arranged parallel to each other have been used for LFC with mixed results. An alternative is to use an actuator with electrodes placed orthogonally to each other. Orthogonally arranged actuators exhibit different jetting characteristics to conventional ones, and as such understanding the effect that these actuators have on the mean velocity profile within a flat plate boundary layer is of significant interest to the development of DBD-based LFC technology. In this investigation, the velocity distribution within a flat plate boundary layer in a zero pressure gradient is measured in response to the operation of an orthogonally arranged actuator. The results suggest that significant thinning of the boundary layer can be realized with an orthogonally arranged actuator, over a short distance downstream of the device, and used in conjunction with a subtle suction effect, this thinning can be exacerbated. However, further downstream, rapid thickening of the layer, supported by a decrease in the shape factor of the flow suggests that the layer becomes unstable, in an accelerated fashion, to the presence of the actuator. Hence the stability of the layer is found to be significantly altered by the presence of the orthogonally arranged actuator, a requisite for a LFC system. However, since the actuator produces a destabilizing effect, the development of a successful LFC system based on orthogonal actuators will require further work.